Implementation of an Enhanced Dynamically Adapted Students’ Admission System - Onyebueke , Agu, Edward; Glory , Nwadialor, Buchim; Timothy , Moses (African Journal of Education,Science and Technology (AJEST), 2016)
The design and implementation of computerized dynamic students’ admission system is aimed at realizing an efficient and accurate computation of students’ results. It saves the school the embarrassment caused by students complaints at the end of working day. These complaints arise from the problems discovered in the manual registration system which not only include inefficiency, inaccuracy, time consumption and inconveniency but labourious and sluggish. These problems are as result of lack of fund and expertise being faced by most private and indigenous universities in some developing parts of the world, ill-management policy to reduce cost and frequent ethno-religious challenges within the Kwararafa University environment as a case study. These problems occasioned the dynamic computerization of the manual system which was achieved in this research in order to solve these problems associated with it owing to the uniqueness of the university as the case study. Adaptation of enhanced RC6 cryptosystem also help to fight against insecurity been faced in so many automated admission systems that exist in other higher institutions. Rapid Application Development (RAD) methodology was used which helped not only in carrying the client along with its concept of Joint Application Development (JAD), but also in delivering a solution that meet the uniqueness of the university requirements within a reasonable time frame. The basic technological tools and features introduced to automate this dynamically enhance admission processing system is the designed problems solving algorithm using Visual C# Programming language on Microsoft .net platform. The result achieved showed a significant improvement over admission processing accuracy, efficiency, reduced administrative cost and timeliness, aims at alleviating the incidences of academic admission lapses which is the bases of socio-economic progress in the history of so many universities in the world which may be facing the same challenges as Kwararafa University, Wukari.